2019
DOI: 10.4103/ijpc.ijpc_159_18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of caregivers' strain during radiation therapy of head-and-neck cancer patients: An institutional report using modified caregivers' strain index scale

Abstract: Aims:Very little works have been reported on the issues of burden perceived by the caregivers of head-and-neck cancer (HNC) patients. Job of the caregiver is complex, and it limits their social, psychological, and economical well-being. Our study aims at assessing caregivers' strain during radiation therapy (RT) of HNC patients using the Modified Caregivers' Strain Index (MCSI) Scale.Materials and Methods:In this single-institutional cross-sectional study, we interviewed caregivers of HNC patients undergoing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…3,4 In the present study, caregivers were predominantly males 55.56%. This is similar to findings of the studies by Unnikrishnan et al and Kazi et al 4,5 In the present study, majority of the care givers (37.15%) were related to the patient as spouse. The findings were similar to studies done by Vahidi et al, Lukhmana et al and Kulkarni et al where it was 38.16%, 38.03% and 33.5% respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3,4 In the present study, caregivers were predominantly males 55.56%. This is similar to findings of the studies by Unnikrishnan et al and Kazi et al 4,5 In the present study, majority of the care givers (37.15%) were related to the patient as spouse. The findings were similar to studies done by Vahidi et al, Lukhmana et al and Kulkarni et al where it was 38.16%, 38.03% and 33.5% respectively.…”
Section: Discussionsupporting
confidence: 93%
“…No significant association was observed between the various socio demographic variables and burden score. The findings was similar to a study done by Kazi et al 5…”
supporting
confidence: 93%
“…[ 45 ] In their study, Kazi and Ghosh found that among the caregivers of the patients diagnosed with head-and-neck cancer receiving radiation therapy, 58.3% experienced physical strain, and 95.8% experienced economic strain. [ 46 ] Bicer and Ozcebe compared the caregivers of cancer patients to the control group and reported that 42% of the caregivers experienced caregiver strain due to the cases such as psychological changes, changes in schedules, and personal plans as well as sleep disorders. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…High MCSI scores were a reflection of increased caregiver strain. Based on the final score, the caregiving strain was classified as low (0-8), moderate (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and high (19)(20)(21)(22)(23)(24)(25)(26). [12] In this study, the moderate and high strain categories were grouped for comparison with the low strain category.…”
Section: Assessment Of Caregiver Strainmentioning
confidence: 99%